(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The yield of wheat also depends on the germination of its seeds, that is, the number of seedlings per 1 m2 of land. Seed germination depends on many factors, one of which is the soil composition and the flatness of the field